Form and rhetorical function of phrase-frames in promotional writing: A corpus- and genre-based analysis. (December 2020) - Casal, J. Elliott; Kessler, Matt
Abstract: A recent trend in corpus-based text analysis emphasizes the recurring linguistic features which writers use in the construction of disciplinary genres in terms of the rhetorical aims realized through their use, with a particular emphasis on formulaic sequences and genres associated with the production and dissemination of academic knowledge. The present study extends this trend into research on an understudied promotional genre by examining the distribution of frequent phrase-frames (p-frames) across the rhetorical stages of 148 purpose statements in accepted Fulbright grant applications. P-frames were automatically identified according to a number of established thresholds and manually filtered for completeness. Each occurrence of the 69 identified p-frames was analyzed in context to assign one of four rhetorical move codes based on previous research. In addition, experienced ESL writing instructors ( N = 10) and advanced ESL learners ( N = 10) were surveyed regarding their perceptions of the pedagogical potential of each p-frame for the teaching of promotional genres. The distribution of these p-frames across the rhetorical stages of the analyzed texts, as well as the learner and instructor ratings, are analyzed and presented here. Overall findings highlight the potential pedagogical value of teaching discontinuous formulaic sequences due to their composition of both fixed and variable elements.